2011
DOI: 10.4103/0976-237x.91795
|View full text |Cite
|
Sign up to set email alerts
|

Flexible denture base material: A viable alternative to conventional acrylic denture base material

Abstract: Although clinician's skills and experience play a major role in designing and fabrication of the optimum prosthodontic restorations, the selection of denture resins is equally important, especially when the patient has been using the prostheses since long. Eighteen cases who were not satisfied with their conventional acrylic dentures were selected. They were provided flexible dentures along with a questionnaire to precisely evaluate the advantages of new material. Prosthodontic planning & observations regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
2
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 7 publications
0
53
2
7
Order By: Relevance
“…Većina relevantnih članaka prikazi su slučajeva ili serije prikaza slučajeva i u njima se vrjednuju fizikalnomehanička svojstava termoplastičnih materijala (11 -14). Kliničku učinkovi-tost i kako pacijenti prihvaćaju PDP-e ili PPP-e izrađene od najlona, u usporedbi s onima izrađenima od akrilatnih smola, procjenjivalo se tijekom 18 mjeseci u dva istraživanja (15,16). U prvom istraživanju (15) autori su izvijestili o samo dvije frakture po središnjoj liniji, dok su mastikacija, fonetika i tolerancija na nošenje bile poboljšane kod savitljivih gornjih pomičnih proteza uz prirodne zube u nasuprotnoj čeljusti.…”
Section: Uvodunclassified
See 2 more Smart Citations
“…Većina relevantnih članaka prikazi su slučajeva ili serije prikaza slučajeva i u njima se vrjednuju fizikalnomehanička svojstava termoplastičnih materijala (11 -14). Kliničku učinkovi-tost i kako pacijenti prihvaćaju PDP-e ili PPP-e izrađene od najlona, u usporedbi s onima izrađenima od akrilatnih smola, procjenjivalo se tijekom 18 mjeseci u dva istraživanja (15,16). U prvom istraživanju (15) autori su izvijestili o samo dvije frakture po središnjoj liniji, dok su mastikacija, fonetika i tolerancija na nošenje bile poboljšane kod savitljivih gornjih pomičnih proteza uz prirodne zube u nasuprotnoj čeljusti.…”
Section: Uvodunclassified
“…Different superscript letters indicate statistical differences between groups in each item of the same column. Same letters mean no difference at a = .05. voljnija cijena (3,16). Statistička analiza pokazala je da je sklonost prema uporabi savitljivih PDP-a bila značajno različita (P < 0,001), ali ne i razlozi za odluku o izradi savitljivoga PDP-a (P > 0,05).…”
Section: Grupe • Groupsunclassified
See 1 more Smart Citation
“…[7] In a study, conducted about the preference among the two types of denture base material; flexible dentures versus conventional acrylic, 100% patients preferred the flexible dentures over customary methyl methacrylate dentures. [8] VII.…”
Section: Frpds Versus Conventional Rigid Acrylic Rpd (Temporaries)mentioning
confidence: 99%
“…As explained by Thakral et al, (17) the flexibility of materials changed the concept of force control from the design features of the appliance to the properties of the base material. This material provide stress breaking action and allowing better stress distribution, act as a tissue conditioner in the long term use due to its slight movement as a result of flexible nature which might allow normal blood circulation underneath it and reduce the tissue atrophy that occur to the non loaded edentulous ridge (18) . This results was attributed with Leticia et al (19) , who found that the colony counts of Candida species were high in the acrylic resin denture bases in HIV patients.…”
Section: Discussionmentioning
confidence: 99%